REMAINING HARMONY AMIDST DEBT TRAPS: PROBLEMS AND STRATEGIES FOR FAMILIES IN MAINTAINING MARRIAGE HARMONY IN THE BANYUMULEK VILLAGERS - Helwinda; Sainun; Muhammad Fikri (Familia: Jurnal Hukum Keluarga, 2025)
This research explores the challenges of intrafamily debt and strategies for building sakinah families among pottery artisan households in Banyumulek Village, West Lombok. As a traditional craft industry center, this community exhibits unique socio-economic characteristics with fluctuating income patterns dependent on tourism seasons, creating distinctive financial vulnerabilities. Using qualitative descriptive methodology conducted from July to September 2023, this study involved five families with significant debt problems (ranging from 50 to 70 million rupiah) who successfully maintained family sakinah. The research integrates Islamic law perspectives and marriage law frameworks in analyzing intrafamily debt issues. The results show that families implement various strategies including: building mutual trust and support, setting clear debt repayment targets, developing positive beliefs about debt resolution, maintaining open communication through deliberation, and strengthening spiritual dimensions. Concrete efforts include opening additional businesses, taking side jobs, allocating income specifically for debt repayment, and implementing strict financial management. The challenges faced include internal conflicts over debt allocation, economic pressures from income fluctuations, and social pressures from community stigmatization. Solutions implemented reflect emotional and spiritual maturity, including commitment to non-violence during conflicts, adaptive financial management strategies, spiritual reinforcement through worship, and mental resilience against negative perceptions. This study contributes empirically by demonstrating that sakinah families maintain harmony not through the absence of financial problems but through adaptive coping mechanisms that integrate Islamic values with practical economic strategies. The study concludes that a sakinah family is identified by the ability to manage challenges while maintaining sakinah, with success correlated with the category of sakinah family according to the Ministry of Religious Affairs classification.